Efektivitas Program Psikoedukasi Secara Online dalam Meningkatkan Penyesuaian Sosial Pada Individu Dewasa Awal Hingga Dewasa Tengah - Siswanti, Dian Novita; Daud, Muh.; Khaerunnisai, Adinda Maulidya (Peneliti.net, 2026)
This research explores the translation shifts in Guantanamo Diary book from English into Indonesian, addressing the differences that occur when meaning is transferred from one language to another in a structured manner. This research highlights the essential strategies of translation for managing the grammatical, cultural, and linguistic differences between a target language (TL) and a source language (SL). The primary aim is to identify the types of shifts that occurred and explain how are the shifts applied in the translation of Guantanamo Diary from English to Indonesian. This research employs J. C. Catford theory on translation shifts, concerning level shifts and category shifts, which includes structure shifts, class shifts, unit shifts, and intra-system shifts. Utilizing a qualitative research method, this research conducts a detailed analysis of translation shifts analysis of the text, focusing on how linguistic and cultural differences between English and Indonesian are systematically addressed in the translation process to achieve accuracy, naturalness, and communicative equivalence. Data collection involves a documentation method with note taking technique, wherein the memoir is examined and searched for translation shifts, which are then categorized and analyzed. This research contributes to the broader discourse on shifts in translations, emphasizing the complex relationship between linguistic, grammatical, and cultural differences. The findings are presented descriptively, aiming to enhance the understanding of how various types of translation shifts applied to overcome linguistic differences and achieve accuracy between English and Indonesian in the themes presented in the novel. Through the analysis, all types of translation shift according to Catford's theory are reflected in Guantanamo Diary.